Laparoscopic pancreatoduodenectomy does not completely mitigate increased perioperative risks in elderly patients. Issue 10 (October 2015) - Tee, May C.; Croome, Kristopher P.; Shubert, Christopher R.; Farnell, Michael B.; Truty, Mark J.; Que, Florencia G.; Reid-Lombardo, KMarie; Smoot, Rory L.; Nagorney, David M.; Kendrick, Michael L.
Abstract: Background: Elderly patients undergoing open pancreatoduodenectomy (OPD) are at increased risk for surgical morbidity and mortality. Whether totally laparoscopic pancreatoduodenectomy (TLPD) mitigates these risks has not been evaluated. Methods: A retrospective review of outcomes in patients submitted to pancreatoduodenectomy during 2007–2014 was conducted ( n = 860). Outcomes in elderly patients (aged ≥70 years) were compared with those in non elderly patients with respect to risk adjusted postoperative morbidity and mortality. Differences in outcomes between patients submitted to OPD and TLPD, respectively, were evaluated in the elderly subgroup. Results: In elderly patients, the incidences of cardiac events (odds ratio [OR] 3.21, P < 0.001), respiratory events (OR 1.68, P = 0.04), delayed gastric emptying (DGE) (OR 1.73, P = 0.003), increased length of stay (LoS, 1 additional day) ( P < 0.001), discharge disposition other than home (OR 8.14, P < 0.001) and blood transfusion (OR 1.48, P = 0.05) were greater than in non elderly patients. Morbidity and mortality did not differ between the OPD and TLPD subgroups of elderly patients. In elderly patients, OPD was associated with increased DGE (OR 1.80, P = 0.03), LoS (1 additional day; P < 0.001) and blood transfusion (OR 2.89, P < 0.001) compared with TLPD. Conclusions: Elderly patients undergoing TLPD experience rates of mortality, morbidity and cardiorespiratory events similar to those in patients submitted to OPD. In elderly patients, TLPD offers benefits by decreasing DGE, LoS and blood transfusion requirements.